Remediation of a Beneficial Use Impairment at Bluffer's Park Beach in the Toronto Area of Concern. Issue 3 (3rd July 2018) - Edge, T. A.; Hill, S.; Crowe, A.; Marsalek, J.; Seto, P.; Snodgrass, B.; Toninger, R.; Patel, M.
Abstract : Bluffer's Park Beach in the Toronto and Region Area of Concern had a history of beach postings often exceeding 80% of the beach season since the 1980s. A study applied expanded E. coli surveillance and microbial source tracking techniques in 2005–2007 to identify fecal pollution sources contributing to beach postings. Expanded surveillance in the beach vicinity identified significant E. coli hotspots in the foreshore beach sand (pore water max E. coli  = 255, 000 CFU 100 ml −1 ) and associated with a marsh inland of the beach. During rain events, streams from the marsh (max E. coli  = 173, 000 CFU 100 ml −1 ) and runoff from the parking lot (max E. coli  = 4100 CFU 100 ml −1 ) were observed to overflow across the beach to contaminate beach waters. Microbial source tracking using library-dependent (antibiotic resistance and rep-PCR DNA fingerprinting of E. coli isolates) and library-independent (human HF183 bacterial DNA marker) methods indicated the prevalence of animal fecal pollution sources at the beach rather than human sewage. These results were consistent with sanitary survey information, observations of wildlife in the marsh area, and Gulls and Canada Geese on the beach. In 2006, a bird management program was initiated, and remedial actions continued in advance of the 2008 bathing season to engineer a berm to prevent marsh runoff into beach water and re-direct parking lot drainage into the marsh. Since these remediation actions, Bluffer's Park Beach has been posted less than 20% of each beach season, and it was awarded a Blue Flag accreditation in 2011.